"Batedoras de Porta" in action: the search for visibility for Sen Çal Kapimi on Twitter - Gato, Ana Clara Moraes Gato (Brasil, 2022)
Globalization has promoted changes in the world television scene, bringing cultures closer together and reducing geographical borders with just a few clicks. Turkey became the second largest exporter of television series in the world, trailing just two from the United States. Still, not in Brazil, the phenomenon in the growth of these series in the open channels has been wandering in comparison to the movement that is far from the Internet, which performs a voluntary job of collecting, producing and sharing content for other families. This work proposes a case study of the fandom of Sen Çal Kapımı, one of the most popular series produced in Turkey in Brazil, with the aim of identifying and understanding the actions carried out by fas to generate visibility to the program on Twitter. The concepts used address issues such as network societies, family communities, participatory culture and convergence culture. Therefore, as methods for collecting data, we carried out a brief ethnographic survey on Twitter and a questionnaire structured by the Google Forms platform, in which it was possible to understand how the mobilizations are organized and which are the main actions carried out by the fans – who call themselves Door Knockers – in the search of the visibility of the series. As a result of two data obtained, four categories were created to assist in the interpretation of the collected information, being them: She makes her own fics; From SÇK to life; Hey Twitter, notice me; and Everywhere. With this, we observed a great non-fandom collaborative work in search of series recognition, which generated results that are considered to be a production sale for more than 80 countries and for HBO Max streaming, as well as the renewal of the series for a second season. Likewise, it seeks to contribute to the studies of families in the context of culture of convergence, tracing new dreams about the families of Turkish series in Brazil.